Chiral 6-NHC Ligand and Copper Complex: Properties, Application, and Mechanism - Park, Jin Kyoon; McQuade, D. Tyler (Synthesis, 2012)
We demonstrated the synthesis of chiral annulated six-membered-ring N-heterocyclic carbenes (6-NHC) and their adducts with water and alcohol. We also have shown the donating properties of chiral annulated 6-NHCs is between that of typical 5-NHCs and 6-NHCs. We have shown the synthetic conditions for 6-NHC–copper complex formation. Using the chiral 6-NHC–copper complex, we synthesized unsaturated chiral bimetallic allylic boronate reagents with high enantioselectivity. Finally, we propose a catalytic cycle that justifies observed reactivity and provides a new explanation for the role methanol has in the reaction cycle; our cycle is supported by a primary kinetic isotope effect.
Keywords: bimetallic reagents; copper; boron; carbene complex; enantioselective substitution